Postoperative Phrenic Nerve Palsy, A Cause Of Prolonged Mechanical Ventilation In Trans-Sternal Thymectomy - Sharma, Mona (Journal of Kathmandu Medical College, 2015)
Post trans-sternal thymectomy, the patient may develop respiratory failure, usually due to myasthenic crisis or cholinergic crisis. These crises may prolong mechanical ventilation and impede on-table extubation. We report a case of respiratory failure due to unilateral phrenic nerve palsy in a case of myasthenia gravis. A 35 year old female, known case of myasthenia gravis was posted for trans-sternal thymectomy. Anaesthesia was induced with Propofol, Fentanyl and low dose of Atracurium. Thymoma was incasing right subclavian vein and was adherent with the pericardium, Masaoka Grade III. Blood loss was approximately 200ml. Immediate post operative period showed low tidal volume, tachypnea and tachycardia in spite of train of four ratio >0.9. Patient was kept intubated with suspicion of myasthenic crisis and the dose of Pyridostigmine was increased, but this lead to increased cholinergic symptoms. Pain was addressed with thoracic epidural analgesia. Chest radiograph done later in the evening showed elevated right hemi diaphragm, thereby, confirming the diagnosis of phrenic nerve palsy. Difficult dissection in this case has resulted in right phrenic nerve palsy. Phrenic nerve palsy has to be considered as a cause of respiratory failure post sternotomy thymectomy, especially in case of Masaoka grade III and IV. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12249 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014, Page: 122-125